2016
DOI: 10.35196/rfm.2016.3.247-252
|View full text |Cite
|
Sign up to set email alerts
|

Tejidos Alternativos Al Foliar Para Evaluar La Respuesta a La Fertilización Con Zn O B en Aguacate Hass

Abstract: Las deficiencias de zinc (Zn) o boro (B) en frutos y hojas de aguacate (Persea americana Mill.) cv. Hass son comunes en la región productora del estado de Nayarit, México. El seguimiento de la concentración foliar de estos micronutrimentos en respuesta a la fertilización no siempre proporciona un diagnóstico adecuado. El objetivo de esta investigación fue evaluar el efecto de la fertilización al suelo con Zn o B sobre la concentración de estos nutrimentos en el tejido de diferentes estructuras de la planta de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…When analyzing the order of limitation in all the areas studied, it was observed that the most deficient element was Zn, followed by B (Table 7). Deficiencies of these two nutrients are common in many subtropical areas where avocado is grown commercially, especially in acid soils with a sandy texture (Crowley et al, 1996;Salazar-García et al, 2014).…”
Section: Order Of Nutrient Limitationmentioning
confidence: 99%
See 4 more Smart Citations
“…When analyzing the order of limitation in all the areas studied, it was observed that the most deficient element was Zn, followed by B (Table 7). Deficiencies of these two nutrients are common in many subtropical areas where avocado is grown commercially, especially in acid soils with a sandy texture (Crowley et al, 1996;Salazar-García et al, 2014).…”
Section: Order Of Nutrient Limitationmentioning
confidence: 99%
“…The total amount of Zn required to achieve an abundant harvest of quality fruits does not represent a problem. The real difficulty lies in ensuring that the tree receives the necessary amount of this element to satisfy its physiological requirements and produce profitable crops (Salazar-García et al, 2014).…”
Section: Fertilization Recommendationmentioning
confidence: 99%
See 3 more Smart Citations